(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article deals with the development and implementation of state education standards and curricula to teaching and educational process on the basis of competence approach. Such trends as competence, competitiveness and morality are considered as the main tasks of continuous education system. Moreover, the article describes modeling of monitoring the quality of education issues.